Remote Thermal Water Leakage Sensor With a Laser Communication System - Awwad, Ameen (2020)
The change in the temperature of an underground water pipeline and its surrounding environment caused by a leakage has been detected by a variety of devices. Among the most popular technologies are infrared cameras, distributed temperature sensing using fiber optic cables, and analog active temperature sensors. In this paper, a novel low-cost leakage detection system composed of two analog active temperature sensors is presented. The proposed system detects water leakages by comparing the readings of two analog active temperature sensors, one at the surface at a depth of 2 cm of a sand layer covering a buried water pipeline and the other is adjacent to the first sensor at the same depth in a thermally insulated portion by a polystyrene barrier. The results of the heat flow simulation developed with FEMM (Finite Element Method Magnetics) 4.2, which is free, open source, cross-platform capable of solving heat flow problems, showed that the addition of the insulation is expected to increase the difference between the readings of the sensors from 0.011 to 0.063 K (°C) when there is a leakage, and thus the addition of the insulation can be effective in making the effect of leaked water on the surface temperature more detectable. Experimental results indicated the capability of the proposed system in detecting water leakage which caused a temperature difference of 1.47 °C after 30 minutes of running a leaking water system. Furthermore, a laser communication system was built to allow for the transmission of an alarm signal from the sensing node above the underground pipeline to a master node which should have an internet connection to upload information to a cloud storage which can be accessed by different users.